Calibration of mammagraphy ionisation chambers - Steenkamp, Maria (My University, 2008)
The South African national calibration facility is currently not equipped for mammography, dose-measuring equipment. A therapy X-ray machine was used as a calibration unit at the national secondary standards dosimetry laboratory (SSDL) for medium and low energy X-ray, therapy calibrations. It is not necessarily intuitive that the latter calibrations are applicable to diagnostic X-ray beams generated by high frequency generators. The response of measuring equipment calibrated in a therapy X-ray beam, compared to its response in a diagnostic or clinical mammography unit, is unknown. The aim of the research was to investigate whether there was a measurable difference between the X-ray beam qualities available for low energy diagnostic radiology and radiation therapy, i.e. up to 100 kV. The beam qualities studied included both mammography and conventional diagnostic radiography, i.e. nominally 20 kV to 100 kV. The diagnostic and therapy X-ray tubes under investigation had different target-filter combinations, inherent filtration and theoretically, different X-ray spectra. Practically, spectrometry of X-ray beams is not possible because of the sophistication of the instrumentation, comprehensive analyses being very time consuming and not practically applicable to the clinical environment (Kharatti and Zarrad, 2003). Furthermore, not all SSDL’s or Hospitals have access to spectral analysers. Clinical beam quality is instead specified in terms of both the tube peak voltage and the half-value layer (HVL), the thickness of material that will reduce the maximum output of the X-ray beam to 50%. The goal was to compare measured HVLl’s to the ones recommended by the International Electro technical Commission (IEC-61267, 2005) for available mammography beam qualities. The method was validated using attenuation curves. The attenuation curves were then used to derive the suitability of the X-ray spectra for calibration of mammography ionisation chambers (Waggener and Blough, 1999). One of the low energy therapy units was found to be suitable for introducing a regional calibration service for mammography.
Keywords: Mammography; calibrations; spectral analysers; beam qualities